2017
DOI: 10.1002/pssa.201700480
|View full text |Cite
|
Sign up to set email alerts
|

Al+Si Interface Optical Properties Obtained in the Si Solar Cell Configuration

Abstract: Al is a commonly used material for rear side metallization in commercial silicon (Si) wafer solar cells. In this study, through‐the‐silicon spectroscopic ellipsometry is used in a test sample to measure Al+Si interface optical properties like those in Si wafer solar cells. Two different spectroscopic ellipsometers are used for measurement of Al+Si interface optical properties over the 1128–2500 nm wavelength range. For validation, the measured interface optical properties are used in a ray tracing simulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Spectra in ε for the aluminum back contact are represented by the parametric expression described by Subedi et al . 37 .
Figure 2Experimental (symbols) spectra measured at 0 T (top-left), +1.48 T (top-right), −1.48 T (bottom-left) and difference spectra measured at ±1.48 T (bottom-right) with their corresponding calculated models (solid lines) of m 12 , m 13 , m 21 , m 22 , m 23 , m 31 , m 32 , m 33 , m 41 , m 42 , and m 43 normalized Mueller matrix elements for the Al-BSF Si wafer solar cell at 50° angle of incidence under dark condition measurement. The unweighted error function for this fit is σ = 4.33 × 10 −2 .
Figure 3Complex dielectric function, ε = ε 1 + i ε 2 , spectra for the phosphorus doped n-type Si emitter layer and boron doped p-type Si bulk wafer obtained from optical Hall effect measurements of the Al-BSF Si wafer solar cell under dark condition and 1 sun illumination (AM1.5 solar irradiance spectrum) measurements.
…”
Section: Resultsmentioning
confidence: 99%
“…Spectra in ε for the aluminum back contact are represented by the parametric expression described by Subedi et al . 37 .
Figure 2Experimental (symbols) spectra measured at 0 T (top-left), +1.48 T (top-right), −1.48 T (bottom-left) and difference spectra measured at ±1.48 T (bottom-right) with their corresponding calculated models (solid lines) of m 12 , m 13 , m 21 , m 22 , m 23 , m 31 , m 32 , m 33 , m 41 , m 42 , and m 43 normalized Mueller matrix elements for the Al-BSF Si wafer solar cell at 50° angle of incidence under dark condition measurement. The unweighted error function for this fit is σ = 4.33 × 10 −2 .
Figure 3Complex dielectric function, ε = ε 1 + i ε 2 , spectra for the phosphorus doped n-type Si emitter layer and boron doped p-type Si bulk wafer obtained from optical Hall effect measurements of the Al-BSF Si wafer solar cell under dark condition and 1 sun illumination (AM1.5 solar irradiance spectrum) measurements.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that reflection loss and parasitic absorption in the conduction and charge carrier transport layers are dominant factors of optical loss in perovskite solar cells. Shockley–Read–Hall recombination due to unpassivated defects in the perovskite absorber layer and other nonradiative recombination at absorber surfaces and interfaces contribute to electronic loss in perovskite solar cells. All the studies related to the optical and electronic losses in perovskite solar cells until now have only focused on the losses via structurally and optically continuous bulk component layers. The presence of surface roughness on a layer leads to physical mixing with overdeposited layers at interfaces that can result in further optical and electronic losses. , Silver (Ag) used as a back electrical contact in perovskite solar cells is known to diffuse and interact with carrier transport layers to form a physically mixed region of Ag and these carrier transport layers. In addition, Ag also interacts with halide ions within the perovskite absorber layer . Similarly, perovskite films deposited by spin-coating methods are reported to form a lower-density layer with larger perovskite grains and lower surface coverage near the substrate. In perovskite solar cells, the optical and electronic losses arising from physical mixing between the component layers and their precise impact on device performance have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A transfer matrix approach based upon input complex optical properties and layer thicknesses obtained from spectroscopic ellipsometry is used to simulate absorbance within each layer of the device. ,,,− ,, The transfer matrix approach is applied here as the physically mixed interfacial layer thickness and the in-plane morphological features are much smaller than the wavelength of light considered for both spectroscopic ellipsometry and EQE. The absorbance from all perovskite-containing layers in a device is summed to simulate the ideal EQE spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ray-tracing software only needs to be run for the baseline cell case to obtain its absorption, and does not need to be run for every new design. The Si cell is 150 μm thick with aperiodic pyramidal surface texture with an angle of inclination of 54.74°, and the refractive index is taken from Schinke et al 34 and Herzinger et al 35 The cell back interface is modeled as 103 nm of an Al−Si alloy with the refractive index taken from Subedi et al 36 with a 0.02 mm thick Al back contact. 37 In the calculation of the cell absorption matrix, light is injected in the encapsulant material directly above the cell.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%